School-Age Homeless Children: Crucial Transporters of Literacy Activities in the Shelter - Warsi, Sadia (Journal of the American Academy of Special Education Professionals, 2007)
While research on emergent literacy development provides a comprehensive picture of the factors that are conducive to children’s early literacy development, environments of young preschool children living in overnight and residential shelters have not been investigated from an emergent literacy perspective. Results of my comprehensive study on the emergent literacy development of children living at a homeless shelter uncovered the role of older school-age children (among other factors) in providing unique opportunities for younger children’s literacy interactions. This article aims to describe these children’s activities in detail in an attempt to promote further research and discussion in the area of homeless children’s educational and literacy development.